Tracking the 2020-2022 Graduate Population of the Bachelor's Degree in English with Business Management Training in Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2024)
The objective of this study is to gather information of the professionals graduated from 2020 to 2022 from the Bachelor in English with Business Management from the University of Costa Rica, Pacific Campus, in order to gather reliable data in terms of their professional careers, further professional development and personal view about possible improvement areas in the curricula that would allow them to achieve the current market demands and would contribute to decision making processes. The information was gathered through a structure questionnaire applied to all the population graduated in the years 2020, 2021 and 2022. The analysis was descriptive, with a quantitative approach, and demonstrated that the Major does permit a quick immersion in the workforce by training bilingual professionals with knowledge in business management, but it suggests a prompt reestablishment of these two areas for a better union of the two disciplines.
Keywords: HIGHER EDUCATION; ENGLISH; BUSINESS MANAGEMENT; BILINGUAL EDUCATION; PROFESSIONS